Pengaruh Penerapan International Financial Reporting Standards (KFRS) Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia - Karolina, Cici Endah Karolina; Nasution , Afrina; Nasution , Lini Elisyah; Hutagalung , Debora Elysa; Olivia, Hastuti (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to examine whether there is an effect of IFRS implementation on financial reports listed on the IDX, especially on company value in the capital market. This study uses the Chow test. The research population is companies that are included in the Food and Beverage industry in the period 2017-2021. The research sample was determined using purposive sampling. Processing was carried out by grouping the data into before the application of IFRS and after the application of IFRS. This research method is quantitative, data processing uses SPSS 26. The research variables measured are Net Profit Margin (X1), Price Book Value (Y). From the research results, it can be concluded that firm value in the Food and Beverage industry is affected by the application of IFRS.